2005
DOI: 10.1051/0004-6361:20042491
|View full text |Cite
|
Sign up to set email alerts
|

The lithium content of the Galactic Halo stars

Abstract: Thanks to the accurate determination of the baryon density of the universe by the recent cosmic microwave background experiments, updated predictions of the standard model of Big Bang nucleosynthesis now yield the initial abundance of the primordial light elements with unprecedented precision. In the case of 7 Li, the CMB+SBBN value is significantly higher than the generally reported abundances for Pop II stars along the so-called Spite plateau. In view of the crucial importance of this disagreement, which has… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
148
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(169 citation statements)
references
References 120 publications
(201 reference statements)
18
148
3
Order By: Relevance
“…In our warm (T eff  5800 K) stars, the mean is log ε Li = 2.2, which is consistent with log ε Li = 2.177±0.071 deduced by Charbonnel & Primas (2005) for the [Fe/H] −1.5 stars with T eff  5700 K. Further theoretical studies of stellar physics and evolution are needed to understand source(s) of discrepancy with the standard BBN that predicts log ε Li = 2.72±0.06 (Coc et al 2012) and discrepancy between the warm and cool (T eff <5800 K) halo dwarf stars.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our warm (T eff  5800 K) stars, the mean is log ε Li = 2.2, which is consistent with log ε Li = 2.177±0.071 deduced by Charbonnel & Primas (2005) for the [Fe/H] −1.5 stars with T eff  5700 K. Further theoretical studies of stellar physics and evolution are needed to understand source(s) of discrepancy with the standard BBN that predicts log ε Li = 2.72±0.06 (Coc et al 2012) and discrepancy between the warm and cool (T eff <5800 K) halo dwarf stars.…”
Section: Discussionsupporting
confidence: 90%
“…Careful reanalysis of the literature data led Charbonnel & Primas (2005) to deduce log ε Li = 2.177±0.071 for the [Fe/H] −1.5 stars with T eff  5700 K. With the baryon-to-photon ratio defined accurately by the Wilkinson Microwave Anisotropy Probe, standard big bang nucleosynthesis (BBN) predicts a primordial lithium abundance of log ε Li = 2.64±0.03 (Spergel et al 2007) to 2.72±0.06 (Coc et al 2012). Several physical mechanisms were proposed to reduce the Li abundance at the surface of halo stars compared with the pristine one (see, e.g., Charbonnel & Primas 2005;Korn et al 2006;Fu et al 2015); however, the theoretical models see considerable difficulties in reconciling a non-negligible depletion of lithium with both the flatness and the small dispersion along the Spite plateau. It is worth noting that the NLTE corrections for the only line, Li I λ6707, used in the abundance determinations are mostly negative and small in absolute value (Figure 2).…”
Section: Stellar Abundance Trendsmentioning
confidence: 99%
“…Figure 3 illustrates how the mean lithium abundance varies with visual magnitude in the cluster and also compares our findings to other, similar studies of NGC 6397. A feature seen in all three of the most recent studies is that subgiants appear more lithium-rich than less evolved stars, as already suggested by Charbonnel & Primas (2005) for field stars. Our observations reveal a small upturn in Li abundance, located just prior to the stage where Li is strongly diluted, which may indicate that an overabundance is formed above Li-free layers in the stellar interior.…”
Section: Results and Implicationssupporting
confidence: 62%
“…15: the Asplund et al (2006) sample is biased, having been purposedly selected not to include objects significantly deviating from the Spite plateau. In fact, stars with varying degrees of Li depletion have long been known to exist (e.g., Charbonnel & Primas 2005). On the other hand, warm (i.e., T eff > 6000 K) dwarf stars deviating from the Spite Plateau appear to be quite rare at [Fe/H] > −3.…”
Section: Discussionmentioning
confidence: 99%